Rancang Bangun Alat Ukur Digital untuk Suhu Tubuh, Berat Badan dan Tinggi Badan Dengan Tampilan LCD dan Output Suara Berbasis Arduino Uno - Raihan Farandy, Muhammad; Marno, Marno; Sena, Boni (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
More and more manually operated equipment is being replaced by automatic equipment due to rapid technological advances. Many equipment, especially devices for measuring body temperature, weight and height, are still operated manually. This is why this concept led to the creation of computerized body measurement devices equipped with LCDs and sound output. Measuring height, weight and body temperature is simpler. The ultrasonic sensor is used to measure height, the load cell sensor is used to measure weight, and the MLX 9016 component is used to detect body temperature in this research. Sensor components are used in measurements. LCD and speakers are used to display information data. Information about weight, height, body temperature and BMI is displayed on the LCD. The sound output is in the form of a speaker, producing sound in the form of BMI result data. The Arduino Uno functions as the brain of the device, allowing it to communicate with other sensor components. The average level of accuracy/success in measuring height is 98.74%, the average percentage of success in measuring body weight is 99.2%, and the percentage of success in measuring body temperature is 99.74%, in accordance with the test results and data collection on the tool This. After considering everything, it was confirmed that the design of the tool was functioning as it should.